2012
DOI: 10.1504/ijcb.2012.046513
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the P300 paradigm for cognitive biometrics

Abstract: Automatic identification of a person's individuality is an important issue today. Brain Computer Interfaces (BCI) which uses EEG as a modality is a promising area for cognitive biometrics. A BCI system could be used to recognise a sequence (say letters, colours or images) by the user. This sequence could form a 'BrainWord', which could be used for authentication in a multimodal environment with other technologies for high security applications. In this work, we studied several variations of the well-known P300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 23 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…It can be further divided into steady state evoked potential (SSEP) and event-related potential (ERP) [124]. EP components are labeled either exogenous or endogenous [125]. Exogenous components are influenced by physical attributes of stimuli such as intensity, modality, and presentation rate.…”
Section: Evoked Potential or Evoked Response (Ep)mentioning
confidence: 99%
“…It can be further divided into steady state evoked potential (SSEP) and event-related potential (ERP) [124]. EP components are labeled either exogenous or endogenous [125]. Exogenous components are influenced by physical attributes of stimuli such as intensity, modality, and presentation rate.…”
Section: Evoked Potential or Evoked Response (Ep)mentioning
confidence: 99%
“…Only a handful of studies have been done where EEG and ECG signals have been used as a source of biometric information. Few researchers who have worked in the area of EEG have reported a success rate of 70-90% [8]- [14]. Similarly, 90-96% success rate has been reported when ECG has been used as a source of biometric information [6] and [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…Distance is set approximately one meter. Based on the studies in [5]- [7] found that the optimal parameter for the subject to reduce visual fatigue or visual discomfort. For each trial, therefore, we set the duty cycle (D) is 0.7, flickering rate (F) is fixed at 7 Hz, light intensity (I) is 10%, and chromatic color (C) is green.…”
Section: Methodsmentioning
confidence: 99%